2023
DOI: 10.3389/fnins.2023.1151892
|View full text |Cite
|
Sign up to set email alerts
|

Management of auricular transcutaneous neuromodulation and electro-acupuncture of the vagus nerve for chronic migraine: a systematic review

David Fernández-Hernando,
Cesar Fernández-de-las-Peñas,
Juan A. Pareja-Grande
et al.

Abstract: BackgroundMigraine is a type of primary headache that is accompanied by symptoms such as nausea, vomiting, or sensitivity to light and sound.ObjectiveThe aim of this study was to conduct a systematic review on the effectiveness of non-invasive neuromodulation, auricular transcutaneous vagus nerve stimulation (at-VNS), and electro-ear acupuncture of the vagus nerve in patients with migraine headaches.MethodsSix databases were searched from inception to 15 June 2022 for clinical trials, in which at least one gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…Besides the technique’s safety, patients in the SA group had increased rates of symptom remission between 6 weeks and 3 months, which may be associated with the delayed effects of AA treatment . We should underscore that in AA, part of the technique’s effect is attributed to stimulating the auricular branch of the vagus nerve, increasing parasympathetic activity while simultaneously decreasing sympathetic nervous system activity . This effect may lead to an improvement in depression-related symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the technique’s safety, patients in the SA group had increased rates of symptom remission between 6 weeks and 3 months, which may be associated with the delayed effects of AA treatment . We should underscore that in AA, part of the technique’s effect is attributed to stimulating the auricular branch of the vagus nerve, increasing parasympathetic activity while simultaneously decreasing sympathetic nervous system activity . This effect may lead to an improvement in depression-related symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [29] Decrease in number of migraine attacks. Fernandez-Hernando et al [30] External Trigeminal Nerve Stimulation NI None reported [26].…”
Section: Methodsmentioning
confidence: 99%
“…Of these, n-cNVS was approved by the Food Drug Administration (FDA) for treatment of migraines in 2018, nearly 21 years after the original technology was introduced [29]. This technique simply necessitates the placement of an electrical stimulation device on the concha or tragus of the ear with the goal of stimulating the auricular branches of the vagus nerve, providing analgesic effects [30].…”
Section: Peripheral Nerve Stimulation (Occipital Nerve Stimulation [O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Isso envolve alternar entre estados de É importante ressaltar que, na prática da acupuntura auricular, uma parcela significativa dos efeitos da técnica tem sido atribuída à estimulação do ramo auricular do nervo vago. Este estímulo tem o efeito de aumentar a atividade do sistema nervoso parassimpático, ao mesmo tempo em que reduz a atividade do sistema nervoso simpático(118,119). A estimulação transcutânea do nervo vago auricular (taVNS) tem demonstrado segurança e eficácia em condições como epilepsia, transtornos depressivos maiores e insônia(120).…”
unclassified